Shearing Behavior at the Interface of Sand-Structured Surfaces Subjected to Monotonic Axial Loading - Abu Qamar, Mu’ath I.; Tamimi, Mohammad F.; Alshannaq, Ammar A.; Al-Masri, Rama O. (Civil Engineering Journal, 2024)
Enhancing the interface shear strength is crucial in the capacity and design of several geotechnical structures when subjected to static loading. The efficiency of these structures can be enhanced by utilizing innovative designs that allow the mobilization of higher interface shear resistance with bio-inspired-engineered or structured (rough) surfaces when compared to conventional smooth or random rough surfaces of the same geometry (i.e., soil-foundation contact area). Bio-inspired-engineered surfaces used in this study are developed after surfaces with snakeskin-inspired and engineered rough designs that maximize the interface shear resistance in cohesionless and cohesive soils. The frictional behavior and resistance of the bio-inspired-engineered surfaces were experimentally evaluated utilizing a modified interface direct shear apparatus on three locally available sand specimens. Results from tests on smooth surfaces against three different sands mobilized almost the same resistance and soil contraction. The results indicate a behavior significantly influenced by the shape and arrangement of the surface features, accompanied by larger resistance and volume dilation. A parametric study on the characteristics of the structured elements on three sands revealed the isolated impact of elements arrangement, shape, and roughness on the maximum attainable interface strength. The surface element characteristic ratio is found to control the load-transfer mechanism between sand and bio-inspired-engineered structured surfaces. Doi: 10.28991/CEJ-2024-010-10-06 Full Text: PDF